On boundary value problems for degenerate differential inclusions in Banach spaces - Valeri Obukhovskii; Pietro Zecca (Abstract and Applied Analysis)
We consider the applications of the theory of condensing set-valued maps, the theory of set-valued linear operators, and the topological degree theory of the existence of mild solutions for a class of degenerate differential inclusions in a reflexive Banach space. Further, these techniques are used to obtain the solvability of general boundary value problems for a given class of inclusions. Some particular cases including periodic problems are considered.